Nurturing Creativity in the Classroom - Beghetto, Ronald A.; Kaufman, James C. (Cambridge University Press, 2012)
"Nurturing Creativity in the Classroom is a groundbreaking collection of essays by leading scholars, who examine and respond to the tension that many educators face in valuing student creativity but believing that they cannot support it given the curricular constraints of the classroom. Is it possible for teachers to nurture creative development and expression without drifting into curricular chaos? Do curricular constraints necessarily lead to choosing conformity over creativity? This book combines the perspectives of top educators and psychologists to generate practical advice for considering and addressing the challenges of supporting creativity within the classroom. It is unique in its balance of practical recommendations for nurturing creativity and thoughtful appreciation of curricular constraints. This approach helps ensure that the insights and advice found in this collection will take root in educators' practice, rather than being construed as yet another demand placed on their overflowing plate of responsibilities"--Provided by publisher.